Tafsir Marāḥ Labīd dalam Diskursus Tajdīd Abad ke-19 - Muhammad Hasani Mubarok; Ahmad Fauzi (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2021)
This paper attempts to elaborate the Marāḥ Labīd of Nawawī al-Bantānī in the context of Islamic reform of the 19th century. The study examines the context behind the emergence of Marāḥ Labīd and its intersection with the narrative of renewal which evolved in Egypt, where Nawawī’s exegesis was firstly published. It then tries to carry out a historical reconstruction by paying attention to how the interpretation is structured, the background and purpose of the exegete in alluding the term of tajdīd in the opening section of exegesis. In addition, the method and approach of interpretation are also analyzed, as both were the strategies to engage with the discourse of tajdīd. This study argues that one of the hallmarks of Marāḥ Labīd lies on its ability to associate the modern traits of interpretation, while at the same time leaning on the episteme of classical interpretation with a concise, solid and clear explanation. It would not be an exaggeration if this interpretation is a brief blend of two currents of interpretation, namely ra’yī and naqlī. It was from this point that Nawawi’s efforts to get involved in the discourse of tajdīd could be understood.